Characteristics of soil microbial communities in farmland with different comprehensive fertility levels in the Panxi area, Sichuan, China - Xu, Yadong; Liang, Taibo; Dai, Huaxin; Zhai, Zhen; Chen, Yulan; Yin, Guangting; Zhang, Yanling; Yue, Caipeng (Frontiers in Microbiology, 2023)
Soil bacterial communities are intricately linked to ecosystem functioning, and understanding how communities assemble in response to environmental change is ecologically significant. Little is known about the assembly processes of bacteria communities across agro-ecosystems, particularly with regard to their environmental adaptation. To gain further insights into the microbial community characteristics of agro-ecosystems soil in the Panxi area of Sichuan Province and explore the key environmental factors driving the assembly process of the microbial community, this study conducted field sampling in major farmland areas of Panxi area and used Illumina MiSeq high-throughput sequencing technology to conduct bacterial sequencing. Soil organic matter (SOM), alkali-hydrolyzed nitrogen (AN), available phosphorus (AP), available potassium (AK) and other environmental factors were determined. The membership function method and principal component analysis method were used to evaluate the fertility of the soil. The results revealed minimal differences in alpha diversity index among samples with different comprehensive fertility indices, while NMDS analysis showed that community differences between species were mainly reflected in high fertility and low fertility (R: 0.068, p: 0.011). Proteobacteria, Acidobacteria and Actinobacteria were the main types of microbial communities, accounting for more than 60% of the relative abundance. Proteobacteria accounted for a higher proportion in the high fertility samples, while Acidobacteria and Actinobacteria accounted for a higher proportion in the middle and low fertility samples. Both the neutral theoretical model and zero model analysis showed that the microbial communities in tobacco-planting soil with different comprehensive fertility indices presented a random assembly process. With the increase in environmental distance difference, the diversity of the microbial community in medium and low-fertility soil also increased, but there was no significant change in high-fertility soil. Redundancy analysis showed that pH and SOM were the key factors affecting microbial community composition. The results of this study can provide a theoretical reference for the study of environmental factors and microbial communities in tobacco-growing soil.